GREEN ECONOMY STRATEGY AS A PILLAR OF TRANSITION TOWARD INDONESIA’S FOOD SECURITY: A LITERATURE REVIEW - Amanda Archangela (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Food security is one of Indonesia’s strategic development issues, facing complex challenges such as climate change, land degradation, and fluctuations in global food prices. The green economy is considered a potential framework for transitioning toward food security by emphasizing resource efficiency, renewable energy, and inclusive governance. This study aims to examine the concepts and strategic approaches of the green economy in supporting the transition toward national food security in Indonesia. The method employed is a systematic literature review of 15 scientific articles published over the past decade, retrieved from Scopus and Google Scholar databases, with relevance criteria focusing on green economy and food security. The findings indicate that green economy strategies in the food sector encompass sustainable agriculture, efficient resource management, renewable energy utilization, food technology innovation, and the strengthening of community-based food governance. However, several challenges remain, including limited access to green technologies for smallholder farmers, weak policy consistency, and regional adaptation disparities. This study concludes that the green economy is not merely a conceptual framework but also a practical strategy for achieving national food security, contributing significantly to the integration of ecological and social perspectives in food policy.